A apropriação da teoria histórico-cultural em pesquisas relacionadas à alfabetização e ao letramento na educação infantil - Souza, Élica dos Santos (2021)
The present master's dissertation had as its research question: How has the so-called "historical-cultural psychology, historical-cultural perspective, historical-cultural approach, historical-cultural matrix, historical-cultural conception, historical-cultural concept", been configured in the studies on literacy and literacy focused on the education of children under 5 years old? And as a general goals to identify and analyze the appropriation of Historical-Cultural Theory (learning, development, teaching of reading and writing) in research on literacy and literacy in early childhood education. Thus, for the development of our goal, we use as methodology, the theoretical-bibliographical research of theses in the Catalogue of Theses and Dissertations of Capes published between 2013 and 2016, which address the issue of literacy and literacy in early childhood education and are also based on the assumptions of Historical-Cultural Theory. As theoretical basis we use the concepts of Historical-Cultural Theory, such as the psychological development of the child, his learning, the acquisition of language, the constitution of his conscience and his perception of the world, in the studies produced by Vigotski, Luria and Leontiev. After our analyses, we consider that the Historical-Cultural Theory was configured in the theses as a tool to characterize the best pedagogical practices to be carried out with children in Early Childhood Education and also to demonstrate that school education is responsible for the construction of scientific knowledge and for the development of higher psychic functions. We also understand that the theses did not go much beyond what the official documents of the MEC, directed to this stage of education, have already presented, in order to obtain new data and results, thus not having a distance, and these aspects are inserted in the so-called "grammar of schooling". We also emphasize that the teacher's role is fundamental and he/she needs to master pedagogical techniques to teach children scientific knowledge and language use skills and metalinguistic concepts.